Lecturer conceptions of and approaches to decolonisation of curricula - Mashiyi, N.F.; Meda, L.; Swart, A. (South African Journal of Higher Education, 2020)
This report forms part of a larger project that investigated lecturer and student conceptions of decolonisation and decolonisation of curricula at subject level in a South African higher education institution. The study adopted an interpretive paradigm and an on-line questionnaire was administered to all the lecturers in a Faculty of Education in the Western Cape. A de-colonial perspective was used as a lens to interpret the data. In general, participants viewed decolonisation as a worthwhile project that can contribute to the development of a socially-just post-colonial and post-apartheid society. Consistent with the fact that knowledge is created differently in different subjects, the findings revealed varied conceptions of and approaches to the decolonisation of curricula among academics. The study concludes that decolonisation is a complex and multi-layered concept. However. if there are shared understandings of what decolonisation of curricula entails in the different disciplines, and consultative, participatory multi-disciplinary/trans-disciplinary approaches to decolonisation are adopted, significant progress will be made in achieving the goal of decolonising university curricula.